Synthesis of Pt–Containing Metals Alloy and Hybrid Nanowires and Investigation of Electronic Structure Using Synchrotron-Based X-Ray Absorption Techniques - Teng, Xiaowei; Du, Wenxin; Wang, Qi (IntechOpen, 2011)
None